Penerapan Sistem Informasi Akutansi dan Kinerja Pegawai Pemerintah Agency Pembangunan Nasional di Kota Dili - Santos, Lilia Pinto Cardoso Dos; Sisdyani, Eka Ardhani; Putri, I Gusti Ayu Made Asri Dwija; Jati, I Ketut (E-Jurnal Akuntansi, 2023)
Senior employees find it difficult to understand the basics of accounting in a system that is supposed to make employees' work easier so they don't work manually. The aim of this research is to determine the influence of the use of accounting information systems, understanding of accounting and the role of information technology on the performance of employees of the Dili National Development Agency as a sample of 100 observers. The research uses quantitative techniques with multiple linear regression analysis. The results of the research show that there is a positive influence on the use of accounting information systems, the role of information technology, the role of information technology on employee performance at the National Development Agency in Dili City. Keywords: Accounting Information Systems, Understanding of Accounting; Role of Information Technology; Performance